The impact of agricultural disasters on child development in rural China - Xu, Sipei; Zhan, Peng (Frontiers in Public Health, 2022)
BACKGROUND: China's uneven development under the urban-rural dichotomy has led to the discouraging development of children in rural areas. China is a large agricultural country and agricultural disasters are relatively common. Rural children aged 10–15 whose families depend on the agricultural economy may experience far-reaching negative effects from these disasters. OBJECTIVE: This study explored the effects of agricultural disasters on rural children’s development, including cognitive and noncognitive skills, and academic pressure. METHODS: Survey data from the China Family Panel Survey and the National Meteorological Administration for 2010–2018 and a fixed-effect panel model with difference-in-differences regressions were used in the study. RESULTS: The fixed effects model results showed evidence that agricultural disasters have a negative impact on rural children’s cognitive and noncognitive skills and a positive impact on academic pressure. The statistically significant coefficients are -0.094, -0.920, and 0.224, respectively. School and family environments also explain children’s development. Robustness tests confirmed these results. CONCLUSIONS: Evidence shows that agricultural disasters have a significant negative impact on rural child development. It may be inferred that these will increase the difficulty of narrowing the urban-rural development gap. China is committed to promoting prosperity for all its people. Special attention should be paid to the consequences of disasters at the child level and appropriate measures should be taken to mitigate possible negative impacts.